Impact analysis of PES in assisting young people in transitioning out of NEET status in Spain - Prieto-Flores, Ò.; Agahi, O.; Braziene, R.; Rodrigues, R. B.; Rocca, A.; Mazzochi, P.; Giovanni; Higgins, O.; Milenkova, V.; Keranova, D.; Beilmann, M.; Edisherashvili, N.; et al. (2nd Italian Conference on Economic Statistics, 2024)
In the recent literature, specific analyses related to the role of Public Employment Services (PES) in supporting transitioning out of NEET status are limited. Accordingly, this current study investigates this topic using a longitudinal survey of young NEETs in Spain. The survey involved 1013 young people throughout two different waves. The findings show the impact of services offered by PES to young people to exit from NEET status.